All-Inside, Remnant-Preserving Posterior Cruciate Ligament Reconstruction - Nikolaos E. Koukoulias, M.D., Ph.D.; Angelo V. Vasiliadis, M.D., Ph.D.; Evangelia Germanou, M.Sc., Ph.D.; Dimitris Koukoulias, P.T.; Theofilos Dimitriadis, M.D. (Arthroscopy Techniques)
Posterior cruciate ligament reconstruction is a demanding procedure with several techniques described so far. The all-inside technique offers the advantage of minimal invasiveness, whereas the remnant-preservation technique results in a stronger construct with superior biology. We present a combination of these 2 techniques with special attention to reproducing the normal anatomy of the posterior cruciate ligament and avoiding injury to the popliteus artery.